Stress level of sales employees due to innovative strategies in automobile sector - DR. GIGI G.S; MS. SHALINI.V (The journal of contemporary issues in business and government, 2020)
Work stress plays a major key role in determining the level of job satisfaction of sales employees in the automobile sector. Sales force is the driving force which generates revenue for the top line growth of the company. The objective of the study is to determine the factors of job stress that causes in the sales employee job’s performance. The research had taken samples of 100 sales employees of the automobile sector and primary data is also used. The various tools used for the study are frequency analysis, mean analysis, T-test, ANOVA and regression analysis. This study states that by conducting the stress management programs periodically for the employees it does help to reduce their personal as well as their Professional stress. Organisation support is one of the major factors which influence one’s organisation outcome. Based on the findings it is clear that enriching welfare measures, maintaining reasonable working hours, and healthy working environment would definitely reduce the stress level of each individual and organisational stress among the sales employees and will also contribute efficiency to the organisation.